Synthesis of Some New 2-Methyl -1,4-benzothiazine-3(1H)- one Derivatives as Potential Vasodilators - M. B. Deshmukh; A. R. Mulik; Savita Dhongade-Desai (E-Journal of Chemistry, 2004)
The increase in the internal diameter of a blood vessel that results from relaxation of smooth muscle within the wall of the vessel is vasodilation. This causes an increase in blood flow and a decrease in systemic vascular resistance. Some substances produced by tissue deprived of fresh blood seem to be responsible for the dilation. Many products of metabolism bring about the action, CO2 and acids are among them. Dilation of vessels is necessary to restore local environment of tissues and normal metabolism. It may prove to be potential in the treatment of different cardiac disorders like atherosclerosis, where, the blood vessels are narrowed due to deposition of plaque of substances like cholesterol etc. 1,4-benzothiazines have been reported to possess wide range of pharmacological and biological activities. Here, we report the synthesis and biological activity of some new arylidenehydrazino-(1H)-1,4-benzothiazines. The synthesized compounds were subjected to a prediction of biological activities. A software application (PASS) was used for this purpose. The relationship between structure and different biological activities was studied and it was found that the arylidenehydrazino-(1H)-1,4-benzothiazines are expected to be potential vasodilators.